Using Gibberellic Acid and Ethephon to Induce Flowers on Tropical Foliage Plants - Richard J. Henny; Jianjun Chen (EDIS, 2011)
Even though they are prized for their beautiful leaves, flowers are induced in tropical foliage plants for breeding and for marketing purposes. This 5-page fact sheet discusses several factors to consider when developing protocols for inducing blooms in tropical foliage crops. Written by R. J. Henny and J. Chen, and published by the UF Department of Environmental Horticulture, October 2011.